Resilience for gender inclusion: Developing a model for women in male‐dominated occupations. Issue 1 (13th April 2021) - Bridges, Donna; Wulff, Elizabeth; Bamberry, Larissa
Abstract: What is resilience in the context of work environments where women face barriers as significant as career discrimination and harassment? In such a context, is resilience an individual responsibility? How can organizations contribute to and support employee resilience? And where is gender in this equation? This conceptual paper explores these questions using aviation, the skilled trades (i.e., carpentry, welding, plumbing) and the military as case studies to understand how gender inclusion could be better supported by resilient organizations. The barriers for women in male‐dominated industries include social exclusion, marginalization, discrimination, harassment, and other forms of social closure. How these barriers can be overcome is not well understood. We argue that individual resilience plays a part in women thriving and developing enduring careers but can only occur in combination with support from gender inclusion strategies and organizational resilience. We have developed the Resilience for Gender Inclusion (RGI) model combining gender inclusion strategies with organizational resilience strategies. The RGI model demonstrates how employee and organizational resilience intersect and may lead to the transformative potential of inclusive cultures of diversity. This will improve employee wellbeing and self‐efficacy and create a much needed sense of belonging and social inclusion for women in male‐dominated occupations.